PRE FEASIBILITY STUDI PEMANFAATN LUMPUR LAPINDO SEBAGAI MATERIAL ALTERNATIVE UNTUK STONEWARE DAN ARTHWAREMUM - Jenny Caroline (Institut Teknologi Adhi Tama Surabaya, 2021)
Lapindo mud waste is hot mud from PT. Lapindo Brantas allegedly contains hazardous materials. Utilization of Lapindo mud waste must be carried out with several tests. Testing on the characteristics of the waste using the Toxicit Characteristic Leadching Procedure (TCLP) test. This research was conducted on a laboratory scale by varying the composition of cement, fine aggregate and Lapindo mud ((1:2:10), (1:3:10), (1:3:9) which were used as bricks and will be tested for absorption. brick brick gravity test, brick surface friction test The results of this study are the average compressive strength of bricks using Lapindo mud with a mixture composition of 10% mud decreased by 18.09 Kg/cm², the composition of the mixture 7.5% mud, namely 18.57 Kg/cm², and 5% mix composition, which is 20.94 Kg/cm², can be categorized as B4 quality bricks (Used for non-weather protected walls), with a standard strength of 21 kg/cm². Meanwhile, the absorption test of all brick compositions meets the requirements SNI is based on SNI 03-0349-1989 regarding concrete bricks (brick), the maximum air absorption rate requirement is 25%.Keywords: Brick, Lapindo Mud, Absorption Test